2017
DOI: 10.1111/coa.12977
|View full text |Cite
|
Sign up to set email alerts
|

Saddle nose deformity and septal perforation in granulomatosis with polyangiitis

Abstract: Background Patients who have granulomatosis with polyangiitis (GPA, syn. M. Wegener) often develop an external nose deformity which may have devastating psychological effects. Therefore, reconstruction of nasal deformities by rhinoplasty may become necessary to achieve a normal appearance. Objective of review The aim of this systematic review was to investigate the efficacy and safety of surgical reconstruction in external nasal deformities and septal perforation in GPA patients. Search strategy A systematic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
0
14
0
8
Order By: Relevance
“…As a general rule, the severity of the saddle nose deformity guides the method of reconstruction and can range from isolated dorsal augmentation onlay techniques, to the use of extended spreader graft techniques when length also needs augmenting 31 and to finally a two-dimensional L-shaped strut technique when length and projection require augmentation. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general rule, the severity of the saddle nose deformity guides the method of reconstruction and can range from isolated dorsal augmentation onlay techniques, to the use of extended spreader graft techniques when length also needs augmenting 31 and to finally a two-dimensional L-shaped strut technique when length and projection require augmentation. 29 …”
Section: Resultsmentioning
confidence: 99%
“…Systematic reviews demonstrate that saddle nose reconstruction in GPA patients with minimal or no local disease is a safe procedure and that L-strut grafts appear to be a more robust technique in the setting of GPA. 29 , 40 The risk of complication decreases with the use of a L-shaped strut reconstruction technique when compared to reconstruction using multiple smaller grafts. 40 The L-strut also affords better stability which resists the resultant scarring and contracture caused by surgery, whereas the placement of smaller and less secure grafts does not offer this stability.…”
Section: Resultsmentioning
confidence: 99%
“…In a systemic review article, good results are reported for calvarial bone and costal cartilage when it comes to external nasal reconstructions for GPA. 21 In general, saddle nose correction is safe and effective in cases of quiescent GPA, and surgery does not appear to either induce a flare-up or accelerate the course of this condition. 22,23 In relation to relapsing polychondritis, surgery has traditionally only been recommended in cases of severe respiratory or cardiac complications, and there has been no study regarding the effectiveness of rhinoplasty with minimal disease activities.…”
Section: Special Considerations Autoimmune-related Saddlingmentioning
confidence: 95%
“…1) [16]. Одновременно с развивающейся седловидной деформацией кожа носа может приобретать синева-тую окраску, что связано с нарушением кровоснабжения этой области [29].…”
Section: варианты поражения вдп при аавunclassified